Profil Kondisi Fisik Dominan Atlet Putra Tim Pon XX Rugby 7’s Papua: Profil Kondisi Fisik Dominan Atlet Putra Tim Pon XX Rugby 7’s Papua - Taplo, Ngawok; Womsiwor, Daniel; Hasan, Baharuddin (JURNAL OLAHRAGA PAPUA, 2023)
This research aims to determine the profile of the dominant physical condition of male athletes from the PON XX Rugby 7 Papua team. The method used is the survey method. The research sample used total sampling, namely 12 athletes. The analysis technique used is quantitative descriptive analysis technique with percentages. The research variables are 5 components of rugby's dominant physical condition which are the test items: Strength, Speed, Power, Agility, Endurance. The results of the study showed that of the 12 athletes, only a few categories met and the remaining 0% or 0 people, including: Strength (squat) athletes were in the category ''very good'' 83.33% or 10 people and the category "poor ” 16.67% or 2 people. Strength (Bench Press) of athletes in the "poor" category is 8.33% or 1 person, "medium" is 25% or 3 people, "good" is 8.33% or 1 person, "very good" is 58.34 % or 7 people. The speed of athletes in the "very poor" category was 16.67% or 2 people, "medium" was 25% or 3 people, "good" was 16.67% or 2 people, "very good" was 14.66% or 5 person. Power (Vertical jump) of athletes in the category "very poor" 16.67% or 2 people, "poor" 16.67% or 2 people, "medium" 50% or 6 people, "good" 16.67% or 2 people. Athletes' agility in the "poor" category was 8.33% or 1 person, "medium" was 41.67% or 5 people, "good" was 25% or 3 people, "very good" was 25% or 3 people. The endurance of athletes in the "very good" category was 8.33% or 1 person. Category "good" 8.33% or 1 person. Category "medium" 33.33% or 4 people. The “less” category is 50% or 6 people. Conclusion The physical condition of the men of the XX PON team of Papuan Rugby Athletes as a whole is classified into 3 categories, namely 12 athletes, there are 3 people or 25% whose physical condition is in the ''poor'' category, 6 people or 50% have the physical condition in the ''good'' category and 3 people (25%) have the ''Very Good” category.